A prospective study of methamphetamine use as a predictor of high school non-attendance in Cape Town, South Africa - Parry Charles D; McKetin Rebecca; Flisher Alan J; Plüddemann Andreas; Lombard Carl J (BMC, 2010)
Abstract Background This prospective study investigated the association between life-long methamphetamine and other drug use and high school non-attendance, in a sample of high school students in Cape Town, South Africa. Methods A random sample of 1535 high school students completed a baseline questionnaire in 2006, and were asked to complete a follow-up questionnaire 12 months later. The questionnaire included questions on substance use, including tobacco, alcohol, methamphetamine and cannabis use, demographic factors, and questions relating to school attendance and performance. Results Forty-three percent of the students surveyed at baseline did not complete a follow-up questionnaire after 12 months. Compared with students who were not using selected substances, an adjusted logistic regression model showed that life-time methamphetamine use in addition to other substances was significantly associated with non-attendance (OR = 2.58, 95% CI: 1.24 - 5.36) when other non-substance use factors (repeating a year at school and being older than the norm for current grade) were taken into account. Conclusions Early identification of students with methamphetamine and other substance use problems, and a supportive rather than punitive school policy, may be valuable in improving high school completion and student retention rates.